Activation functions of photodegraded carboxymethyl cellulose in solution: Viscosity measurements - Elashhab, Fathi; Sheha, Lobna; Sheltami, Rasha; Alfazani, Tahani; Youssef, Abdelsallam (Journal of Pure & Applied Sciences, 2023)
Carboxymethyl cellulose (CMC) is used in several applications exposed to light and radiation, such as food and medical products. The exposure to photons could affect the CMC properties and behaviour therefore the products. Our main objective is to investigate the relative viscosity/temperature relationships of CMC fragments in a NaCl solution. The method of photodegradation technology has been used, and the data were attained viscometrically. The decrease in macromolecular mass and concentration brought down the reduction in solution viscosity, while the temperature had the opposite effect. Eyring's parameters as functions of concentration and molar mass were then illustrated. The enthalpy and Arrhenius factor have increased with increasing concentration and molar mass, while the entropy has decreased. The polyelectrolytic CMC fractions in salt solutions behaved like polymers in neutral solutions. The photodegraded solution of CMC had better solvation quality than the native one.